PENGARUH UNDANG-UNDANG NOMOR 7 TAHUN 1983 TENTANG PAJAK PENGHASILAN SEBAGAIMANA TELAH DIUBAH TERAKHIR DENGAN UNDANG-UNDANG NOMOR 36 TAHUN 2008 TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK (DJP) JAWA TIMUR I - FARISKA SEPTARINA RAJIANTO (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Tax Laws changes made Direktorat Jenderal Pajak (DJP) in order to create Tax Laws that allows taxpayers to carry out their tax obligations and in accordance with the state of today's dynamic economy. One of the Tax Laws amended is Income Tax Law seen from the taxable income bracket; non-taxable income; income tax rates; depositing and reporting procedures; tax audits; tax penalties; Taxpayer behavior; nationality; and taxpayer perceptions of the tax system significantly influence the individual taxpayer compliance in Kantor Wilayah DJP Jawa Timur I. This study continues research Barbuta-Misu (2011) which identifies the variables of tax compliance by creating a model that comes with the factors that affect tax compliance in several countries and adapted to the conditions of the State of Rome. The results of this study states that the taxable income bracket; nontaxable income; income tax rates; depositing and reporting procedures; and tax penalties have a significant influence on the individual taxpayer compliance. Other hand, tax audits; Taxpayer behavior; nationality; and taxpayer perceptions of the tax system that does not have a significant influence on the individual taxpayer compliance. Based on these results, the variables generated in the course of a study conducted by BarbutaMisu (2011) not all variables can affect tax compliance in accordance with the Income Tax Law in force in Indonesia.